ANALISIS DAMPAK ADANYA EKOWISATA MANGROVE PADA KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DI DESA PASIR KABUPATEN MEMPAWAH - Ramadhani, Gita; Bahari, Yohanes; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the impact of mangrove ecotourism on the socio-economic aspect of Desa Pasir Mempawah Hilir society. The method that will be used in this research is descriptive. Data collection techniques that will be used are observation, interview, and documentation. The data collection tools that will be used in this research are the observation guide, interview guide, and documentation. Data analysis will be data reduction, data display, and verification.Keywwords: Impact, Mangrove Ecotourism, Society.